Nothopanax scutellarium: Natural Hair Growth Plant - Wijianto, Diski Wahyu; Wahyuni, Arifah Sri; Sukmawati, Anita; Bakar, Fazleen Izzany Abu (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Hair plays an important role in supporting appearance and self confidence, but problems with hair loss and slow hair growth still often occur; Mangkokan leaves (Nothopanax scutellarium) are known to contain flavonoids such as quercetin which can stimulate hair growth through various mechanisms, and nanoemulsion formulations have been shown to increase the absorption of these active compounds, so this study aims to examine the effectiveness of mangkokan leaves on hair growth through a systematic review based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines with a literature search until November 16, 2024 in the Emerald Publishing, SpringerLink, EBSCO, Cochrane, ProQuest, Science Direct, Scopus, and PubMed databases, of the 68 articles found, only 5 studies met the inclusion criteria after screening, and the results showed that the formulation of mangkokan leaves in the form of ethosomal gel or phytosome lotion at a concentration of 25% was most effective in stimulating hair growth with a mechanism involving the activation of endothelial nitric oxide synthase (eNOS) to increase blood supply to follicles, regulation of nitric oxide (NO) balance and decreased inflammation by quercetin, inhibition of the enzyme 5-alpha reductase to reduce dihydrotestosterone (DHT) levels, as well as increasing the expression of growth factors such as insulin-like growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF), keratinocyte growth factor (KGF), and hepatocyte growth factor (HGF), which overall support the extension of the anagen phase (active hair growth phase) and improve hair health, so that mangkokan leaves have high potential as an active ingredient in hair care products, although further research is still needed to ensure their long-term safety and effectiveness.